Repetitive transcranial magnetic stimulation (rTMS) in the treatment and diagnosis of eating disorders in athletes and patients: a systematic review - Vanessa Teixeira Müller; Clóvis de Albuquerque Maurício; Rodrigo Cunha de Mello Pedreiro; Ciro José Brito; Diego Valenzuela Pérez; Esteban Aedo Muñoz; Otávio de Toledo Nóbrega; Bianca Miarka (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Repetitive Transcranial Magnetic Stimulation (rTMS) is a non-invasive technique used to treat and diagnose eating disorders (EDs) by targeting brain regions like the dorsolateral prefrontal cortex, which is involved in impulse control and emotion regulation. Particularly beneficial for athletes, rTMS can reduce symptoms of EDs. Therefore, this study aimed to carry out a systematic review of the scientific literature on the therapeutic or diagnostic use of rTMS in athletes and patients with EDs, with an emphasis on binge eating disorder (BED), anorexia nervosa (AN), and bulimia nervosa (BN). A literature survey was carried out in the Directory of Open Access Journals (DOAJ), Medline, Directory of Open Access Scholarly Resources (ROAD), Academic Search Premier, Wiley-Blackwell Full Collection, Nature Open Access, BioMed Central Open Access, and Cumulative Index to Nursing and Allied Health Literature (CINAHL). A total of 26 original papers published until November 21, 2021, were included. The selected studies were grouped for each respective protocol: total number of patients or athletes, sociodemographic aspects of the participants, parameters performed in rTMS: type of coil, intensity, frequency, number of pulses, stimulation site, preliminary results, and incidence of adverse effects. Recent evidence suggests a low rate of side effects with the technique and a substantial high frequency rTMS response in both the dorsolateral prefrontal cortex and the ventromedial region, especially in studies where internal comparison was performed. The great tolerance and safety of neuromodulatory treatment with rTMS encourage the application of the technique, especially in patients with refractory eating disorders. In addition to the therapeutic potential, rTMS is an essential diagnostic tool in elucidating the complex neurobiology of eating disorders. A more significant increase in publications on the subject is expected in a controlled, blind, and randomized manner, leading to a homogenization of results and generalization of its potential use.